Impact of Corporate Social Responsibility on profitability of banks in Pakistan: Application of GMM Approach - Mehreen Nazish; Muhammad Hanif Akhtar (iRASD Journal of Management)
The present study investigates the effects of corporate social responsibility (CSR) on financial performance of commercial banks in Pakistan employing the generalized method of moments (GMM) estimator on a panel data. A diverse sample of 25 banks is selected for the analyses for a period of 11 years (2010-2020) based on consistently available data. In addition to the CSR index, some bank-specific and macroeconomic variables are used as control variables to test for the effects of CSR initiatives on profitability of banks in Pakistan. Our findings demonstrate that the CSR drives and commitments on social expectations reward the banks with larger profit margins. Consequently, the results tend to validate the stakeholder theory where socially responsible enterprises lead towards greater financial performance. The control variables like capital intensity, credit risk, bank size, liquidity, age of the bank, proportion of non-executive directors, tangibility and GDP growth divulge mixed results. The diversity in results propose a number of policy and managerial implications both for policy makers and banks managers.